Design of FAIR low-energy cooler-buncher with simulations - Ruotsalainen, Jouni (2021)
A radiofrequency quadrupole cooler-buncher is a device used in low-energy ion beamlines, with the purpose of improving the quality of an ion beam. In this work, the geometry of the functional structure for such a device to be installed at the FAIR facility in Germany was designed using an ion trajectory simulation software SIMION. The goal of the simulations was to determine such a geometry and operational parameters that ion bunches of short temporal spread and small kinetic energy distribution could be created, while maintaining high transmission efficiency. In addition to finding optimal parameters, the effect of some key parameters on the bunch quality was assessed. Using an incoming beam of singly charged ions with mass 100 u having 5 keV energy and 17 π·mm·mrad transverse emittance, a temporal width of 43 ns could be achieved, with a transmission of 96 %. The energy distribution of the bunch was 30 eV and the transverse emittance 9 π·mm·mrad with a kinetic energy of 5 keV. It was found that the gas pressure inside the device and the shape of the electric potential during the extraction of the bunch had the greatest effect on the bunch quality. Compared to other RFQ cooler-bunchers currently in use, for example the JYFL cooler and the ISCOOL at ISOLDE, the achieved temporal spread was slightly lower and the transmission efficiency higher, while the energy spread was larger. As the simulated geometry was found to work well, the actual device can be constructed based on the model created in this work. With some adjustment, the optimised operational parameters obtained in this work can be used in the actual device.